2013
DOI: 10.1108/jhom-jul-2012-0132
|View full text |Cite
|
Sign up to set email alerts
|

Achieving organisational competence for clinical leadership

Abstract: The paper makes clear that clinical leadership was not perceived to be about vesting leadership skills in individuals, but about ensuring health care organisations were equipped to conceptualise and support a model of distributive leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 60 publications
2
61
0
1
Order By: Relevance
“…The third measure was Self-efficacy, measured with the 10-item Schwarzer and Jerusalem scale 27 , with a Cronbach's alpha of 0.881. Emotional Intelligence was suggested through the program planning processes 18 as a key characteristic for clinical leaders and was the fourth measure using the Assessing Emotions Scale. 28 The Cronbach's alpha for the 33 items was 0.899 and all items were retained.…”
Section: Measures: Intermediate Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The third measure was Self-efficacy, measured with the 10-item Schwarzer and Jerusalem scale 27 , with a Cronbach's alpha of 0.881. Emotional Intelligence was suggested through the program planning processes 18 as a key characteristic for clinical leaders and was the fourth measure using the Assessing Emotions Scale. 28 The Cronbach's alpha for the 33 items was 0.899 and all items were retained.…”
Section: Measures: Intermediate Outcomesmentioning
confidence: 99%
“…16,17 Finally, there is increasing evidence that clinical leadership does not just rest with individuals, but that there are organisational requirements for effective clinical leadership. 18 In particular, studies have identified essential system and organisational support that values and sustains the work of clinician leaders distributed throughout the organisation. 3 The review of the literature led to our research question: Can practising health professionals develop leadership skills that have a positive impact on the quality and safety of health service and care delivery in their organisation?…”
mentioning
confidence: 99%
“…Learning and developing is configured in a major challenge for members of educational institutions, and for the learner. 1,7 The key attributes necessary to exercise leadership in the early career are: communication, self-confidence and intelligence. As challenges, they cited: young age, initial acceptance of difficulty of the team, lack of technical skill and experience, and organizational structure of the institution.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, regarding the nursing work, management skills constitute an important guiding principle of effective and efficient practice, highlighting the leadership. 1 Based on the National Curriculum Guidelines (Diretrizes Curriculares Nacionais -DCNs), nursing education has as one of its many goals the exercise to develop skills such as: communication, leadership, decision making, lifelong education, administration and management. 2 The DCN of nursing establish reputable skills such as knowledge, abilities and attitudes, and enable interaction and multidisciplinary activities for the benefit of individuals and communities, promoting health for everyone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation